2010
DOI: 10.1159/000319794
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Type IV Collagen in Nondiabetic Kidney Disease

Abstract: Background: Type IV collagen is one of the major components of basement membrane. In diabetic nephropathy, it is already known that urinary excretion of type IV collagen increases with the disease progression. However, in nondiabetic kidney disease, urinary type IV collagen (u-IVc) levels have not been extensively investigated. The aim of this study was to evaluate u-IVc levels in various nephropathies except diabetic nephropathy. Methods: u-IVc levels were measured cross-sectionally from 527 biopsy-proven non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 42 publications
1
13
0
5
Order By: Relevance
“…Increased urinary and serum concentrations of procollagen type III N-terminal propeptide (PIIINP) reflecting the expression of collagen type III, a typical scar collagen up-regulated in renal fibrosis, may also reflect fibrogenesis in renal allografts (400-402). Collagen type IV, a major constituent of the renal basement membrane, was shown to be elevated in the urine and to be associated with renal function in diabetic nephropathy and patients with glomerulonephritides (403)(404)(405)(406). Interestingly, although several other collagens and ECM proteins are deposited in renal fibrosis and undergo disease-specific modifications, including crosslinking, this has not yet been widely exploited as a potential source of biomarkers.…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%
“…Increased urinary and serum concentrations of procollagen type III N-terminal propeptide (PIIINP) reflecting the expression of collagen type III, a typical scar collagen up-regulated in renal fibrosis, may also reflect fibrogenesis in renal allografts (400-402). Collagen type IV, a major constituent of the renal basement membrane, was shown to be elevated in the urine and to be associated with renal function in diabetic nephropathy and patients with glomerulonephritides (403)(404)(405)(406). Interestingly, although several other collagens and ECM proteins are deposited in renal fibrosis and undergo disease-specific modifications, including crosslinking, this has not yet been widely exploited as a potential source of biomarkers.…”
Section: Serum and Urine Biomarkersmentioning
confidence: 99%
“…It has been demonstrated that serum and urine levels of the collagen type III pro-peptide (surrogate markers for active collagen formation) are increased during renal fibrosis [1113]. In addition, urinary collagen type IV has been associated with loss of renal function [1417]. Such non-invasive biomarkers could enable frequent monitoring of renal patients and facilitate clinical trials studying the effect of antifibrotic therapies.…”
Section: Introductionmentioning
confidence: 99%
“…44 The present study included non-diabetic glomerulopathy patients as well as diabetic nephropathy patients. The results of the present study demonstrate that a preferential decrease in nighttime BP levels was accompanied by decreases in urinary protein and albumin excretion and urinary type IV collagen excretion, an important marker of renal injury in diabetic nephropathy and non-diabetic renal disease, 45,46 without any decrease in eGFR resulting from the olmesartan add-on therapy. The results of the ACCOMPLISH study indicated that not only a reduction of albuminuria but also long-term preservation of eGFR are important for the suppression of CKD progression and cardiovascular complications.…”
Section: Discussionmentioning
confidence: 49%